An Empirical Analysis of IPO Under-Pricing: New Evidence from 2007 NASDAQ Stock Market - Wang, Zhijie (2008)
Initial Public Offering (IPO) has been adopted by most firms when they are process of going public into the stock market. In most cases, the offering price of IPO is systematically lower than its closing price on the first trading day. Because of this, investors can enjoy great benefits by purchasing IPOs on the first trading day and sell them on the second trading day or few trading days later. This phenomenon is called IPO under-pricing and it has been extensively documented in almost every stock market. This paper first reviews the U.S. IPO market. Then, reasons of IPO under-pricing based on several important IPO literatures are explained. Finally, a sample test to analyze the IPO under-pricing condition in U.S. NASDAQ will be carried out. This study examines 117 IPOs issued in the NASDAQ Global Market in 2007. The average under-pricing level is 15.48%. According to the regression result, it is found that 1) there is a significantly positive relationship between offering price and degree of IPO under-pricing; 2) there is a significantly positive/negative relationship between offering price adjustment and degree of IPO under-pricing; 3) there is a significantly negative relationship between economy crisis and degree of IPO under-pricing.